(3GdbhGfjf GdeMceI aj GdCUhds - (3Gdbej, Gdbej, CHh GdbGSe Hf eMeO MSjf Gdbej, J (B1231(3g` (B1816(3es
(3ChdgG (B:s
(3ChdgG(B: (3Cbhd hbO CTQfG Edi HYV gPg GdeWGdH bHd GdYKhQ Ydi gPG GdcdGe aj GdeHMK GdSGHb hChQOfG Ydi eG fbdfG ef HYV cdeGJg aj TQM GdOQhS eG jOaYs
(3BNQgG (B:s
(3BNQgG(B: (3dCf gPG GdebdO dG jecfg Cf jYde GHJOGA Cf Pdc SGQb dg hgh NGFa Yf GdGbOGe Ydi Pdc hdG jecfg Cfg SbhW GdYbGH Yfg (B.. (3Ke GdGYJbGO dCfg EfeG jecfg Cf jYde Pdc EPG YQa GdCUhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 183s
(3GdPQjYI, L (B17: 132s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs